Prevalence of Extensively Drug-Resistant Tuberculosis: a Descriptive Study - O. A. Pasechnik; A. A. Zimoglyad; I. V. Yarusova; S. V. Vitriv; A. I. Blokh (Эпидемиология и вакцинопрофилактика, 2018)
Background. Extensively drug-resistant tuberculosis (XDR-TB) is a threat to community health. Goal. The estimation of the prevalence of extensively drug-resistant tuberculosis in Omsk region, along with the clinical and epidemiological description of patients with XDRTB. Methodology. A retrospective descriptive epidemiologic research of tuberculosis morbidity in Omsk region in 2006–2017 was conducted.Results. The prevalence of extensively drug-resistant tuberculosis in Omsk region in 2006–2017 was stable at 35.6 per 100ths population with Tinc.=1.0%. The prevalence of extensively drug-resistant tuberculosis in Omsk region was 13.6 per 100ths population (n = 267). Among patients with XDR-TB the majority was of young working age 25–44 years (63.2%), male gender (80.9%), officially unemployed (75.6%), ill for at least 3 years (57.0%), suffering from infiltrative pulmonary tuberculosis (69.2%) and HIV-infected (31.8%). The resistance to seven first and second line antituberculosis drugs was found in 10.1% of patients with XDR-TB. Conclusions. The optimisation of approaches to the organization of additional measures for the prevention of extensively drug-resistant tuberculosis is needed.